Transformation of Vestibular Signals for the Control of Standing in Humans - Forbes, Patrick A.; Luu, Billy L.; Van der Loos, H.F. Machiel; Croft, Elizabeth A.; Inglis, J. Timothy; Blouin, Jean-Sébastien (The Journal of neuroscience, 2016)
During standing balance, vestibular signals encode head movement and are transformed into coordinates that are relevant to maintaining upright posture of the whole body. This transformation must account for head-on-body orientation as well as the muscle actions generating the postural response. Here, we investigate whether this transformation is dependent upon a muscle's ability to stabilize the body along the direction of a vestibular disturbance. Subjects were braced on top of a robotic balance system that simulated the mechanics of standing while being exposed to an electrical vestibular stimulus that evoked a craniocentric vestibular error of head roll. The balance system was limited to move in a single plane while the vestibular error direction was manipulated by having subjects rotate their head in yaw. Vestibular-evoked muscle responses were greatest when the vestibular error was aligned with the balance direction and decreased to zero as the two directions became orthogonal. This demonstrates that muscles respond only to the component of the error that is aligned with the balance direction and thus relevant to the balance task, not to the cumulative afferent activity, as expected for vestibulospinal reflex loops. When we reversed the relationship between balancing motor commands and associated vestibular sensory feedback, the direction of vestibular-evoked ankle compensatory responses was also reversed. This implies that the nervous system quickly reassociates new relationships between vestibular sensory signals and motor commands related to maintaining balance. These results indicate that vestibular-evoked muscle activity is a highly flexible balance response organized to compensate for vestibular disturbances. SIGNIFICANCE STATEMENT The postural corrections critical to standing balance and navigation rely on transformation of sensory information into reference frames that are relevant for the required motor actions. Here, we demonstrate that the nervous system transforms vestibular sensory signals of head motion according to a muscle's ability to stabilize the body along the direction of a vestibular-evoked disturbance. By manipulating the direction of the imposed vestibular signal relative to a muscle's action, we show that the vestibular contribution to muscle activity is a highly flexible and organized balance response. This study provides insight into the neural integration and central processing associated with transformed vestibulomotor relationships that are essential to standing upright.